OC-097 The novel gastrin/CCK2 receptor antagonist YF476 induces clinical responses and is well tolerated in patients with type I gastric neuroendocrine tumours. (28th May 2012) - Moore, A R; Ball, L; Boyce, M; Varro, A; Pritchard, D M
Abstract : Introduction: Autoimmune chronic atrophic gastritis causes loss of gastric parietal cells and results in achlorhydria, increased antral gastrin production and hypergastrinaemia. In some patients this hypergastrinaemia induces hyperplasia of enterochromaffin-like (ECL) cells and leads to type I gastric neuroendocrine (carcinoid) tumour (NET) development. Most type I gastric NETs behave in an indolent fashion, but a small proportion (<1%) grow more rapidly and metastasise. Surgical antrectomy has been shown to lead to resolution of hypergastrinaemia and regression of tumours in some patients. We therefore hypothesised that pharmacological inhibition of the gastrin/CCK-2 receptor using the novel orally bioavailable competitive antagonist YF476 would also lead to clinical regression of type I gastric NETs. The aims of this study were to assess (1) whether YF476 is an effective medical treatment for type I gastric neuroendocrine tumours; (2) the safety and tolerability of YF476 treatment and (3) the effects of YF476 on biomarkers of ECL cell activity. Methods: Following ethical committee and MHRA approval, six patients with small type I NETs secondary to autoimmune chronic atrophic gastritis and hypergastrinaemia have received a 12-week course of 50 mg/day YF476. Clinical responses were monitored by six weekly upper GI endoscopy with biopsy and three weekly measurement of fasting serum gastrin and chromogranin A (CgA) concentrations. Drug tolerability has been assessed by monitoring clinical adverse events and by assessing haematological, renal and hepatic blood parameters. Results: In all six patients the number and size of NETs decreased following 12 weeks of therapy (mean reduction in size of largest tumour = 39%, mean reduction in tumour number = 40%). However no patient showed complete tumour regression after 12 weeks' therapy. Serum CgA concentrations decreased in all subjects while receiving YF476, but increased to pre-treatment levels in the three subjects in whom measurements have to date been performed 12 weeks after completing therapy. Fasting serum gastrin concentrations did not significantly change while patients received YF476. YF476 was well tolerated in all patients; no serious adverse effects were reported and there was no evidence of haematological, renal or hepatic toxicity. Conclusion: YF476 is a promising new medical treatment for type I gastric neuroendocrine tumours. It appears to be well tolerated with no observed toxicity. Further trials of YF476 involving more prolonged treatment regimes are therefore warranted in this condition. Competing interests: A Moore grant/research support from: Trio Medicines Ltd., L Ball: None declared, M Boyce: None declared, A Varro: None declared, D Pritchard: None declared.